Forest volume estimation techniques with special emphasis on the tropics - Guzmán Santiago, Juan Carlos; Aguirre Calderón, Oscar Alberto; Vargas Larreta, Benedicto (Universidad Autónoma Chapingo, 2020)
Introduction: Volume is an important variable in forest management since it allows evaluating the growth and development of individuals in stands. Objective: To analyze the techniques for estimating forest volume with an emphasis on the tropics. Materials and methods: The work was developed with the non-probabilistic snowball technique, in which the bibliography reported in an investigation suggested the search for similar works to enrich the subject. Results and discussion: In tropical forests, tree measurement variables provide valuable information for estimating stem or total volume using a xylometer, Pressler and standing tree volume formulas, dendrometric bodies, rigorous volume estimation, graphical method or conventional equations and neural networks. Accurate volume information is only obtained with the xylometer technique, which is the only one that allows estimating volume using the direct method. The rigorous volume estimation technique is the most used in the tropics to obtain the volume of individual sections, which are fitted by conventional or neural network equations to estimate the total volume. Most researchers selected the best models using the coefficient of determination, root mean square error, bias, Durbin-Watson test, and Akaike and Bayesian information criteria. Conclusion: Model selection depends directly on the researchers; however, the xylometer technique is the only one that estimates volume with the direct method and in an accurate way.